Proposed new interior design scheme of makeup studio and academy at 26-8A 8B 8C, Jalan Theatre, 30300 Ipoh. Perak for Nora Bridal Creation Sdn. Bhd / Aida Hayati Mohd Hashim - Mohd Hashim, Aida Hayati (Faculty of Architecture, Planning and Surveying, 2012)
Makeup artist is an whose medium is the human body, applying makeup and prosthetics for theatrical, television, film, fashion, magazines and other similar productions including all aspects of modeling industry. Awards given for this profession in the entertainment industry include the Academy Award for Makeup and even the modeling industry. In the United States as well as the other parts of the globe, professional licenses by makeup academy in order for them to hire the Make Up Artist (MUA). Makeup studio and academy is a commercial place for learn about makeup. There are many makeup studio and academy in Malaysia likes Make Art, SS Image Professional Makeup Academy, M.A.C. Studio and last but not lease Nora Bridal Makeup Studio and Academy. Even though in Malaysia have many makeup studio and academy, but the knowledge about makeup in Malaysia is still poor.